METHODICAL TOOLKIT OF RESEARCH OF ADAPTATION LEVELS FOREIGN STUDENTS TO STUDY IN UKRAINIAN UNIVERSITIES - Xing, Zhefu (Continuing Professional Education: Theory and Practice, 2019)
The article describes the essence of adaptation of foreign students to the structure of education in Ukrainian universities, which is a state of interaction between the individual and the group, in which the individual performs its lead productive activities to meet their own needs, in a state of self-affirmation and free expression. Approaches to the study of foreign students adaptation to study at Ukrainian universities: behaviorist, interactionist, psychoanalytic, humanistic, cognitive. The criteria of the study adaptirovannostiinostrannyh students to study in Ukrainian universities (cognitive, communicative, motivational, activity), performance (knowledge of the essence of a culture shock, knowledge of the Ukrainian social norms, traditions, awareness of learning objectives in the university; awareness about the conditions of the organization of training in high school, the ability to independently communicate in the language of the host country; Maturity of tolerance, the ability to build interpersonal relationships with faculty, students, active in extracurricular activities, the pursuit of the perfect mastery of the Ukrainian language, the motivation to succeed, the desire to achieve the goal, motivation to learn their future profession), levels (high, medium, low) adaptation of foreign students to study in Ukrainian universities. Streamline the system of diagnostic methods for determining the levels of adaptation of foreign students to study in Ukrainian universities. Comparisons of quantitative and qualitative performance indicators defined criteria derived from the results of diagnostic cause the formation of adaptation of foreign students to study in Ukrainian universities